Sistem Pendeteksi Kecelakaan Kendaraan Bermotor Menggunakan Arduino Dan Smartphone Android - Mochammad Taufiq Ardiansyah Amir; Yusrila Yeka Kerlooza (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2020)
Abstract - Many motor vehicle accidents occur in Indonesia. One of the factors causing the high number of accidents is the large number of motorized vehicle users. Accident reporting is currently still hampered by reporting. This research creates an accident reporting system that is fast and automatic to a web server. This study aims to create a system that can report accident locations. Next, the preparation of the machine condition status detection device. And the web server receives the coordinates of the crash site. This system combines an android smart phone with an Arduino microcontroller. In this research, the voltage sensor is used to overcome the motor vehicle battery voltage. Machine condition data transmission status from device to android smart phone using bluetooth HC-05. Accelerometer and GPS sensors on android smartphones are used to check acceleration and location coordinates during an accident. This study uses 4 vehicle conditions while moving. Vehicle traveling normally, sudden brake, front collision and side collision. The speed limit value used in this study is 19.04 m / s2 or 1.94 g. Based on the research results, when the vehicle is running normally there is no significant change in the value of acceleration. In a sudden brake condition, the Y axis of the acceleration sensor decreases in value until the acceleration value is negative. In the hit-front condition, the Y-axis value has increased significantly. Meanwhile, in a side hit condition, the value of the X and Y axes has increased significantly. The front and side crash conditions were tested 10 times each. Front hit conditions were identified as accidents by 80%. While the side hit condition was identified as an accident as much as 100%. Keywords: sensor, accelerometer, accident, GPS, Android smart phone.